Slow spin relaxation of paramagnetic centers in graphene oxide. (November 2019) - Augustyniak-Jabłokow, Maria A.; Tadyszak, Krzysztof; Strzelczyk, Roman; Fedaruk, Ryhor; Carmieli, Raanan
Abstract: Paramagnetic centers in graphene oxide (GO) were studied by continuous wave and pulsed electron paramagnetic resonance (EPR) in the temperature range 4.2–300 K. Saturation of the EPR signal indicates long spin relaxation times of the paramagnetic centers and show that the relaxation times increase with lowering temperature as well as with decreasing the number of water molecules by drying. Long spin-lattice and phase memory relaxation times in deeply dried GO are quantitatively studied by the pulsed EPR techniques. The spin-lattice relaxation time is found to decrease from 52 ms at 5 K to 0.153 ms at 240 K and is dominated by the direct process below 100 K. The T 5 dependence observed at higher temperatures can result from Raman processes. The phase memory time is about 1 μs at 240 K, changes non-monotonically with lowering temperature, and reaches its maximum of 2.2 μs at 5 K. Molecular motions of the functional groups and the adsorbed water molecules are employed to explain this dependence. The paramagnetic centers are attributed to the unfunctionalized carbons in the highly functionalized regions of GO. Their interactions with protons are confirmed by ESEEM. Slow relaxation extends possible applications of GO for quantum computing and spintronics. Graphical abstract: Image 101463